Pengaruh Diferensiasi Jasa Dan Nilai Pelanggan terhadap Kepuasan Pelanggan Serta Dampaknya Pada Loyalitas Pelanggan Jasa Freight Forwarding Pada PT Sandin Indonesia di Jakarta - Hubaullah . (Politeknik Kelapa Sawit Citra Widya Edukasi, 2017)
The purpose of this research is to find the influence of services differentiation and customer value to customer satisfaction and its impact on customer loyalty to PT Sandin Indonesia in Jakarta. The sampling techniques used in this research was accidental sampling and the sample of the about 145 consumers. Technique analysis research using path analysis by software SPSS + AMOS 20. The results of the study showed that that services differentiation and customers value have had a positive impact on customer satisfaction freight forwarding to PT Sandin Indonesia. This indicates that the services differentiation and value customers will have an influence on the increased customer satisfaction , so also on the other hand the decline in services differentiation and value customers will result in the customer satisfaction .Based on the results of the analysis the , be seen that services differentiation and customers value having the effect on customer loyalty. Customer satisfaction having the effect on customer loyalty. This proved the level of satisfaction felt by consumers , so will increase customer loyalty.